2021
DOI: 10.21608/ejchem.2021.84783.4139
|View full text |Cite
|
Sign up to set email alerts
|

Nano-formulations of hesperidin and essential oil extracted from sweet orange peel: Chemical Properties and Biological Activities

Abstract: Citrus EOs and Flavonoids are widely recognized for their beneficial effects in possessing many biological activities, such as antioxidant, antimicrobial and cytotoxic properties, also using in food additives and in the cosmetic industry. The aim of this work is to produce nanoparticles of hesperidin and citrus EO extracted from waste orange peels, and study its biological impact compared to native products (hesperidin and citrus EO) as antioxidant, antimicrobial and cytotoxic. Obtained products (nanoformulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…For cytotoxicity assays using nanoparticles, regularly breast cancer cells are used. However, it has already been shown that cancer lines such as MCF-7 can be induced apoptosis with nanoparticles, and the same nanomaterial does not present any cytotoxic effect in non-cancer lines such as MCF-12F and MCF-10A [ 46 , 47 ]. In a recent study, the fibroblasts exposed to biosynthesized copper nanoparticles displayed uniform growth and normal morphology, reflecting good biocompatibility [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cytotoxicity assays using nanoparticles, regularly breast cancer cells are used. However, it has already been shown that cancer lines such as MCF-7 can be induced apoptosis with nanoparticles, and the same nanomaterial does not present any cytotoxic effect in non-cancer lines such as MCF-12F and MCF-10A [ 46 , 47 ]. In a recent study, the fibroblasts exposed to biosynthesized copper nanoparticles displayed uniform growth and normal morphology, reflecting good biocompatibility [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was cooled at 4 °C for 24 h and ground in a refrigerated mortar. Finally, the product was sieved using a stainless-steel sieve (230 mesh), stored at room temperature in an airtight container 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant, increases the shelf life of food products and this is a good opportunity to benefit from the waste of fruits and vegetables to fortify food products. (2) shows the chemical tests of mango peel powder and the treatments of the fortified cake product, which include protein, fat, moisture, ash, carbohydrates and fiber. Through the results, it is noted that the protein and fat content of the treatments increases with the increase in replacement rates (10,20,30%) compared to the control treatment, Fortifying wheat with mango peel powder improves the of protein and also leads to an increase in the percentage of fat in the treatments, and this is due to the mango peels containing a percentage of fat, and this was confirmed by a study [25].…”
Section: Examination Of the Active Ingredientsmentioning
confidence: 99%
“…Mango peels are high in polyphenols, carotenoids, dietary fiber, vitamin E, vitamin C, essential amino acids and polyunsaturated fatty acids. In addition to containing antioxidant properties due to the presence of many biologically active compounds in the pulp and peel of the mango such as gallic acid, gallotanin, quercetin, ingiverin, and ellagic acid, it has an important role in inhibiting free radicals and has IOP Publishing doi: 10.1088/1755-1315/1158/11/112005 2 antibacterial activity against some types of gram-positive and gram-negative bacteria, yeasts and molds [2,3]. Synthetic antioxidant compounds such as butyl hydroxyl toluene (BHT) and butyl hydroxyl anisole (BHA) are often used in processed foods, these compounds have some carcinogenic side effects, which has led to a growing interest in natural antioxidants found in fruits and vegetables due to their safety, nutritional and therapeutic value [4].…”
Section: Introductionmentioning
confidence: 99%